Hubungan Antara Kualitas Pelayanan Kesehatan dengan Tingkat Kepuasan Pasien Rawat Jalan di UPTD Puskesmas Pati 1 - Ersa Wahyu Nurcahyani; Retno Issroviatiningrum; Muh. Abdurrouf; Muh Abdurrouf (Journal of Medical Practice and Research, 2025)
This study aims to determine the relationship between the quality of health services and the level of satisfaction of outpatients at the Pati 1 Community Health Center (UPTD Puskesmas Pati 1). The quality of health care services is a key determinant in shaping the level of patient satisfaction. The assessment of this quality is not solely based on the achievement of medical interventions, but also includes the attitudes of health care personnel, the timeliness of service delivery, as well as the condition and comfort of the facilities. This study used a quantitative method with a cross-sectional design. The study population consisted of all outpatients at the Pati 1 Community Health Center in April 2025, totaling 173 patients, with a sample of 121 respondents determined using the Slovin formula and accidental sampling technique. The research instruments were a health service quality questionnaire and a patient satisfaction questionnaire. Data analysis was performed using the Spearman Rank correlation test. The results showed that most respondents rated the quality of health services as good (62.8%) and patient satisfaction as satisfied (53.7%). The Spearman Rank test results showed a p-value of 0.000 (<0.05) with a correlation coefficient of 0.692, indicating a strong and positive relationship between the quality of health services and the level of patient satisfaction. The better the quality of services provided, the higher the level of outpatient satisfaction.